2020
DOI: 10.1057/s41599-020-0499-z
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition and confidence ratings predicted by vocal stimulus type and prosodic parameters

Abstract: Human speech expresses emotional meaning not only through semantics, but also through certain attributes of the voice, such as pitch or loudness. In investigations of vocal emotion recognition, there is considerable variability in the types of stimuli and procedures used to examine their influence on emotion recognition. In addition, accurate metacognition was argued to promote correct and confident interpretations in emotion recognition tasks. Nevertheless, such associations have rarely been studied previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 86 publications
3
26
0
Order By: Relevance
“…Present acoustic measures and lexical norms are sufficient for inferring and predicting threat comprehension, but they cannot provide a full account of the prosody and semantics of anger, which may be composed by a myriad of features establishing more complex and nuanced relations (Lausen and Hammerschmidt, 2020). Having stated this, the present analogy between bidimensional features of prosody and semantics is further confirmed by SAM and classification tasks.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Present acoustic measures and lexical norms are sufficient for inferring and predicting threat comprehension, but they cannot provide a full account of the prosody and semantics of anger, which may be composed by a myriad of features establishing more complex and nuanced relations (Lausen and Hammerschmidt, 2020). Having stated this, the present analogy between bidimensional features of prosody and semantics is further confirmed by SAM and classification tasks.…”
Section: Discussionmentioning
confidence: 79%
“…Hence, the present model should be understood as derived from more complex previous models (e.g. Banse and Scherer, 1996;Hammerschmidt and Jürgens, 2007;Lausen and Hammerschmidt, 2020), in such a way that it retains inferential capacity (though not fully descriptive) and facilitates prediction. This could provide useful insights into emotional expression/comprehension, which may be extended from threat or 'hot anger' to other emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though arguments for superior decoding of emotions from nonverbal vocalisations over speech prosody have been put forward, there is little research formally testing this notion. Studies conducted to date have found that negative emotions are recognised more accurately (Hawk, van Kleef, Fischer, & Schalk, 2009;Lausen & Hammerschmidt, 2020;Sauter, 2007) and rapidly (Castiajo & Pinheiro, 2019;Pell, 2015) from nonverbal vocalisations compared to speech prosody. For positive emotions, this perception advantage of nonverbal vocalisations has been tested for happiness/joy and pride, yet it is not established whether it generalises to other positive emotions.…”
Section: Nonverbal Vocalisations Vs Speech Prosodymentioning
confidence: 99%
“…Even though arguments for enhanced communication of emotions via nonverbal vocalizations as compared to speech prosody have been put forward, there is little research formally testing this notion. Studies conducted to date have found that negative emotions are recognized more accurately (Hawk et al, 2009 ; Lausen & Hammerschmidt, 2020 ; Sauter, 2007 ) and rapidly (Castiajo & Pinheiro, 2019 ; Pell et al, 2015 ; Schaerlaeken & Grandjean, 2018 ) from nonverbal vocalizations compared to speech prosody. For positive emotions, this perception advantage of nonverbal vocalizations has been tested for happiness/joy and pride, yet it is not established whether it generalizes to other positive emotions.…”
Section: Introductionmentioning
confidence: 99%